2022
DOI: 10.1371/journal.pone.0270221
|View full text |Cite
|
Sign up to set email alerts
|

Daily physical activity is negatively associated with thyroid hormone levels, inflammation, and immune system markers among men and women in the NHANES dataset

Abstract: The acute effects of exercise on metabolic energy expenditure and inflammation are well studied, but the long-term effects of regular daily physical activity on metabolic and endocrine effects are less clear. Further, prior studies investigating the impact of daily physical activity in large cohorts have generally relied on self-reported activity. Here, we used the U.S. National Health and Nutrition Examination Survey (NHANES) to investigate the relationship between daily physical activity and both thyroid and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 37 publications
1
15
0
1
Order By: Relevance
“…Indeed, it is known that thyroid function could be affected by physical exercise despite its physiologic responses are difficult to characterize fully [39,40]. A recent study showed that physically active adults tended to have lower TSH and T4 levels and at low levels of T4 seem to produce less TSH [41]. These results suggest that physical activity may affect metabolic energy expenditure through effects on thyroid hormone signaling [41].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is known that thyroid function could be affected by physical exercise despite its physiologic responses are difficult to characterize fully [39,40]. A recent study showed that physically active adults tended to have lower TSH and T4 levels and at low levels of T4 seem to produce less TSH [41]. These results suggest that physical activity may affect metabolic energy expenditure through effects on thyroid hormone signaling [41].…”
Section: Discussionmentioning
confidence: 99%
“…In healthy human subjects, acute bouts of exercise transiently increase inflammation, while regular exercise may act as an anti-inflammatory treatment ( Walsh et al, 2011 , Campbell and Turner, 2018 , Klasson et al, 2022 , Sellami et al, 2021 , Zhao et al, 2012 , Chastin et al, 2021 , Shimizu et al, 2008 , Simpson et al, 2020 , Ferreira et al, 2018 , Cantó et al, 2018 , Scheffer and Latini, 2020 , Nieman and Pence, 2020 , Nieman and Wentz, 2019 , Suzuki, 2018 , Cerqueira et al, 2019 ). Acute bouts of exercise elicit a cascade of inflammatory events measured by changes in PBMC counts, lymphocyte subpopulations (T cells, B cells, natural killer (NK) cells), granulocyte, neutrophil and NK cell activity, lymphocyte proliferation, and cytokine levels in plasma ( Nieman, 1997 , Gabriel and Kindermann, 1997 , Pedersen, 1991 , Gonçalves et al, 2019 , Moldoveanu et al, 2001 ).…”
Section: Human Studiesmentioning
confidence: 99%
“…Since regular exercise has the capacity to modulate immune function to enhance anti-inflammatory activity of immune cells in healthy people and animal models ( Walsh et al, 2011 , Calcaterra et al, 2022 , Klasson et al, 2022 , Campbell and Turner, 2018 , Zhao et al, 2012 , Shimizu et al, 2008 , Sellami et al, 2021 , Chastin et al, 2021 , Oliveira-Fusaro et al, 2020 , Sluka and Gregory, 2015 , Gregory et al, 2018 , Gregory et al, 2015 , Leung et al, 2016 , Leung et al, 2016 , da Silva et al, 2015 , Nijs et al, 2014 , Polli et al, 2019 , Clark et al, 2017 , Liu and Wang, 1987 , Kohut et al, 2001 , Baek et al, 2020 , Cannon and Kluger, 1984 ), it is important to determine if regular exercise modulates the immune system in chronic pain populations. Prior randomized controlled trials using various modes of exercise ranging from aerobic (cardiorespiratory), muscle strengthening, stretching, and aquatic based exercise show varying effects on immune function.…”
Section: Human Studiesmentioning
confidence: 99%
“… 140 , 141 , 142 , 143 , 144 In contrast, daily PA positively impacts the immune system. 145 , 146 , 147 Several studies reported positive effects, such as higher levels of natural killer cells (NKs), neutrophils, lymphocytes, monocytes, and plasma interleukin-6, as well as an increased function of NKs and a decrease in inflammation. 28 , 148 , 149 , 150 , 151 Thus, several studies additionally focused on investigating whether PA is related to COVID-19 outcomes and severity.…”
Section: Physical Activity and Covid-19mentioning
confidence: 99%